Ultrasonic instruments and devices : - Papadakis, Emmanuel P. (Academic Press, 1999)
Shows examples of the successful commercialization of devices and instruments arising from previous research in ultrasonics. The first chapter consists of six essays that provide advice on the ways and means of bringing inventions out of the laboratory and onto the showroom floor. The remaining eight chapters illustrate how devices come to fruition, discussing medical ultrasonic diagnostics, nondestructive testing, industrial process control sensors and systems, fabrication and characterization of transducers, surface acoustic wave technology, frequency control devices, industrial ultrasonic imaging/microscopy, and research instruments and systems.Book News, Inc.r, Portland,